Answer:
The tangent line to the given curve at the given point is
.
Step-by-step explanation:
To find the slope of the tangent line we to compute the derivative of
and then evaluate it for
.
Differentiate the equation.
Differentiate both sides.
Sum/Difference rule applied: ![(f(x)\pmg(x))'=f'(x)\pm g'(x)](https://tex.z-dn.net/?f=%28f%28x%29%5Cpmg%28x%29%29%27%3Df%27%28x%29%5Cpm%20g%27%28x%29)
Constant multiple rule applied: ![(cf)'=c(f)'](https://tex.z-dn.net/?f=%28cf%29%27%3Dc%28f%29%27)
Applied power rule: ![(x^n)'=nx^{n-1}](https://tex.z-dn.net/?f=%28x%5En%29%27%3Dnx%5E%7Bn-1%7D)
Simplifying and apply constant rule: ![(c)'=0](https://tex.z-dn.net/?f=%28c%29%27%3D0)
Simplify.
Evaluate y' for x=4:
![y'=4(4)-7](https://tex.z-dn.net/?f=y%27%3D4%284%29-7)
![y'=16-7](https://tex.z-dn.net/?f=y%27%3D16-7)
is the slope of the tangent line.
Point slope form of a line is:
![y-y_1=m(x-x_1)](https://tex.z-dn.net/?f=y-y_1%3Dm%28x-x_1%29)
where
is the slope and
is a point on the line.
Insert 9 for
and (4,10) for
:
![y-10=9(x-4)](https://tex.z-dn.net/?f=y-10%3D9%28x-4%29)
The intended form is
which means we are going need to distribute and solve for
.
Distribute:
![y-10=9x-36](https://tex.z-dn.net/?f=y-10%3D9x-36)
Add 10 on both sides:
![y=9x-26](https://tex.z-dn.net/?f=y%3D9x-26)
The tangent line to the given curve at the given point is
.
------------Formal Definition of Derivative----------------
The following limit will give us the derivative of the function
at
(the slope of the tangent line at
):
![\lim_{x \rightarrow 4}\frac{f(x)-f(4)}{x-4}](https://tex.z-dn.net/?f=%5Clim_%7Bx%20%5Crightarrow%204%7D%5Cfrac%7Bf%28x%29-f%284%29%7D%7Bx-4%7D)
We are given f(4)=10.
![\lim_{x \rightarrow 4}\frac{2x^2-7x-4}{x-4}](https://tex.z-dn.net/?f=%5Clim_%7Bx%20%5Crightarrow%204%7D%5Cfrac%7B2x%5E2-7x-4%7D%7Bx-4%7D)
Let's see if we can factor the top so we can cancel a pair of common factors from top and bottom to get rid of the x-4 on bottom:
![2x^2-7x-4=(x-4)(2x+1)](https://tex.z-dn.net/?f=2x%5E2-7x-4%3D%28x-4%29%282x%2B1%29)
Let's check this with FOIL:
First: ![x(2x)=2x^2](https://tex.z-dn.net/?f=x%282x%29%3D2x%5E2)
Outer: ![x(1)=x](https://tex.z-dn.net/?f=x%281%29%3Dx)
Inner: ![(-4)(2x)=-8x](https://tex.z-dn.net/?f=%28-4%29%282x%29%3D-8x)
Last: ![-4(1)=-4](https://tex.z-dn.net/?f=-4%281%29%3D-4)
---------------------------------Add!
![2x^2-7x-4](https://tex.z-dn.net/?f=2x%5E2-7x-4)
So the numerator and the denominator do contain a common factor.
This means we have this so far in the simplifying of the above limit:
![\lim_{x \rightarrow 4}\frac{2x^2-7x-4}{x-4}](https://tex.z-dn.net/?f=%5Clim_%7Bx%20%5Crightarrow%204%7D%5Cfrac%7B2x%5E2-7x-4%7D%7Bx-4%7D)
![\lim_{x \rightarrow 4}\frac{(x-4)(2x+1)}{x-4}](https://tex.z-dn.net/?f=%5Clim_%7Bx%20%5Crightarrow%204%7D%5Cfrac%7B%28x-4%29%282x%2B1%29%7D%7Bx-4%7D)
![\lim_{x \rightarrow 4}(2x+1)](https://tex.z-dn.net/?f=%5Clim_%7Bx%20%5Crightarrow%204%7D%282x%2B1%29)
Now we get to replace x with 4 since we have no division by 0 to worry about:
2(4)+1=8+1=9.